Fraud di Pemerintahan Analisis Meta: Studi di Indonesia - Natasya Febriola Haurissa; Christine Novita Dewi (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
The aim of this research is to study the determinants of fraud in government sector using 8 years observation period. The purpose of this research is to examine the association between appropriateness of compensation, internal control system, organizational ethical culture, distributive justice, procedural justice, internal control compliance, organizational commitment, leadership style, law enforcement, unethical behavior, information asymmetry, pressure, opportunity, rationalization, performance accountability, regional income, e-government, internal audit, audit response, public official wages, collusion, ability to pay debt, individual morality, negative motivation, irregularities, risk assessment, control activities, monitoring, cash control systems, good governance, needs, and greed to fraud in government sector. This research accumulates and integrates existing studies using Meta Analysis techniques on 35 articles published between 2012-2019. Result of this study confirms the fraud triangle theory, as pressure, opportunity, and rationalizations are factors of fraud occurrence. Other variables that influence the fraud occurrence are the eligibility of compensation and unethical behavior. There are 17 variables that have been tested and robust to be a factor that influence fraud occurrence in government sector. This research can be used as a consideration of steps to be taken to prevent the occurrence of factors that can cause fraud in the government sector.